Knowledge about dietary fibre and its health benefits: A cross-sectional survey of 2536 residents from across Croatia - Ljubicic, Marija (2017)
This cross-sectional study is aimed at identifying the level of understanding of the health benefits of dietary fibre in the prevention of disease, as well as the association between that understanding and fibre consumption in the Croatian population. We believe that nutritional knowledge is important for the consumption of healthy food which includes also a positive reflection on food habits and health. Only well-informed consumers can shop effectively for food rich in dietary fibre and thereby derive the health benefits that fibre can offer. We suppose the association between that understanding and fibre consumption in the Croatian population. However, this knowledge is not the only important determinant; food purchases are influenced by socioeconomic and demographic factors. Our hypothesis is that the level of knowledge about fibre and fibre consumption varies with age, gender, education level and urban or rural environment. It is our assumption that life styles, environmental conditions and education can affect the level of knowledge and perception about healthy eating habits. If this assumption is accurate, targeted education campaigns to educate and sensitise the population about fibre-rich foods and the health benefits of fibre is a priority. Public health programmes are urgently needed, particularly in rural areas, to sensitise the population to fulfill the recommended fibre intake, high-fibre food sources and the mechanisms by which fibre can help prevent disease.